Arquitectura Tecnológica Para Big Data - Camargo-Vega, Juan José; Camargo-Ortega, Jonathan Felipe; Joyanes-Aguilar, Luis (Revista Científica, 2015)
The term Big Data with each passing day, it becomes more important, which is why in this research is studied, analyzed and disclosed in a comprehensive manner the different architectures of Big Data, with its features, tools, technologies and standards related to that end, for the sole purpose of providing assistance to the business sector for possible implementation of Big Data.